Transcriptional Changes in the Transition from Vegetative Cells to Asexual Development in the Model Fungus Aspergillus nidulans - Garzia, Aitor (American Society for Microbiology, 2013)
Morphogenesis encompasses programmed changes in gene expression that lead to the development of specialized cell types. In the model fungus Aspergillus nidulans, asexual development involves the formation of characteristic cell types, collectively known as the conidiophore. With the aim of determining the transcriptional changes that occur upon induction of asexual development, we have applied massive mRNA sequencing to compare the expression pattern of 19-h-old submerged vegetative cells (hyphae) with that of similar hyphae after exposure to the air for 5 h. We found that the expression of 2,222 (20.3%) of the predicted 10,943 A. nidulans transcripts was significantly modified after air exposure, 2,035 being downregulated and 187 upregulated. The activation during this transition of genes that belong specifically to the asexual developmental pathway was confirmed. Another remarkable quantitative change occurred in the expression of genes involved in carbon or nitrogen primary metabolism. Genes participating in polar growth or sexual development were transcriptionally repressed, as were those belonging to the HogA/SakA stress response mitogen-activated protein (MAP) kinase pathway. We also identified significant expression changes in several genes purportedly involved in redox balance, transmembrane transport, secondary metabolite production, or transcriptional regulation, mainly binuclear-zinc cluster transcription factors. Genes coding for these four activities were usually grouped in metabolic clusters, which may bring regulatory implications for the induction of asexual development. These results provide a blueprint for further stage-specific gene expression studies during conidiophore development.